PENDAMPINGAN KAJIAN KITAB NAHWU DI MADRASAH TARBIYYATUL ULAA DEREPAN MENOREH SALAMAN MAGELANG - Yulia Choirun Nisa; Ahmad Saifudin (khidmatan, 2021)
Education is a conscious and systematic effort to foster, assist and guide a person in developing his potential. Education does not only focus on formal learning in schools. The importance of education and introduction to religion motivates parents to entrust their children to study and deepen their religious knowledge in Madrasah Diniyyah, such as the one in Derepan Hamlet, Menoreh Village, Salaman District. In Dusun Derepan, there is Madrasah Diniyyah Tarbiyyatul Ulaa as a forum for students to study religion such as the Qur'an, Iqra, Tajwid and so on. The students who study at the madrasa do not come from that hamlet alone, there are some students who come from neighbouring hamlets. In terms of the quantity of the madrasa, it makes the devotees move to examine the actual learning methods used by the madrasa so that it has its own charm for the students who study there. Based on this, the servant provides assistance by contributing to the learning of the yellow book with the aim of increasing the relationship between caregivers, ustadzah, students and special servants.